The pilot study "Determinants of consumer purchase decision for private label brand (PLB) product" - Yusoff, Azahar; Abu Bakar , Hatinah; Che Cob , Che Mohd Syaharuddin; Ab Aziz, Alinawati; Azahar, Nuramira Farhana (Journal of Islamic, Social, Economics and Development, 2026)
This pilot study is emphasizing on consumer purchase decision of Private label brand product in Kelantan and, emphasizing on selection of attributes which an indicator of purchasing decision. Private Label Brand (PLB) is a company’s who are selling product or services under their retailer or wholesaler name. However, despite the availability and affordability of these products, the acceptance rates of Private Label Brand (PLB) products among Malaysian consumers are still considered relatively low when compared to other countries in the Asia region and in certain state in Malaysia consumer are suffering especially B40 and M40 due to limited income to buy the product. This study needed to assist consumer in making decision with limited income to decide what product should be purchase to fulfil their needs and wants. Thus, this study examines the relationships perceived quality, perceived value, perceived risk, price, brand image and purchase decision and the mediating of willingness to buy towards purchase decision among consumer in Kelantan whereby it is known as second lowest income state in Malaysia. This pilot study is needed in order to test the element involved in questionnaires and the model Theory of Consumption Value (TCV) and Theory of Reason Action (TRA), fit with the research objectives and design. A quantitative and questionnaire survey method was employed for 30 respondents in this study and final analysis using the structural equation model partial least square (SEM-PLS) through purposive sampling method. The findings, the results show that in the context of consumer purchase decision of Private Label brand in Kelantan, the attributes such as perceived quality, perceived risk, and price significantly influence, while perceived value and brand image are significant and consider relevant to be used in further investigations.